Normal Distribution Approximation through Binomial and Poisson Distribution - Musadi Musadi; Ira Kurniawati (Journal of Mathematics and Mathematics Education, 2023)
Abstract: The purpose of this research is to prove the approach of normal distribution through binomial distribution and Poisson distribution both theoretically and inductively. The research method used is a literature study by collecting various literature related to the problem under study. Theoretically, the binomial distribution and the Poisson distribution will be closer to the normal distribution when ???? approaches infinity or in other words the limit ???? towards infinity of the binomial distribution or Poisson distribution will approach the normal distribution. Theoretically, this approach can be proven by the method of generating moments. While inductively, the approach can be seen from the polygons of the binomial distribution and Poisson distribution which will increasingly approach the normal curve when the amount of data is very large approaching infinity.